Impaired Adrenergic/Protein Kinase A Response of Slow Delayed Rectifier Potassium Channels as a Long QT Syndrome Motif: Importance and Unknowns - Policarová, Marcela; Novotný, Tomáš; Bébarová, Markéta (The Canadian journal of cardiology, 2019)
The slow delayed rectifier potassium current (IKs) significantly contributes to cardiac repolarization under specific conditions, particularly at stimulation by the protein kinase A (PKA) during increased sympathetic tone. Impaired PKA-mediated stimulation of IKs channels may considerably aggravate dysfunction of the channels induced by mutations in the KCNQ1 gene that encodes the structure of the α-subunit of IKs channels. These mutations are associated with several subtypes of inherited arrhythmias, mainly long QT syndrome type 1, less commonly short QT syndrome type 2, and atrial fibrillation. The impaired PKA reactivity of IKs channels may significantly increase the risk of arrhythmia in these patients. Unfortunately, only approximately 2.7% of the KCNQ1 variants identified as putatively clinically significant have been studied with respect to this problem. This review summarizes the current knowledge in the field to stress the importance of the PKA-mediated regulation of IKs channels, and to appeal for further analysis of this regulation in KCNQ1 mutations associated with inherited arrhythmogenic syndromes. On the basis of the facts summarized in our review, we suggest several new regions of the α-subunit of the IKs channels as potential contributors to PKA stimulation, namely the S4 and S5 segments, and the S2-S3 and S4-S5 linkers. Deeper knowledge of mechanisms of the impaired PKA response in mutated IKs channels may help to better understand this regulation, and may improve risk stratification and management of patients suffering from related pathologies.
Keywords: mutace; beta-adrenergní receptory; draslíkový kanál KCNQ1; pozdní usměrňovače draslíkových kanálů; převodní systém srdeční; Heart Conduction System; lidé; Long QT Syndrome; proteinkinasy závislé na cyklickém AMP; KCNQ1 Potassium Channel; Receptors, Adrenergic, beta; fosforylace; Cyclic AMP-Dependent Protein Kinases; syndrom dlouhého QT; Mutation; Phosphorylation; Delayed Rectifier Potassium Channels; Humans